2 - 2 * 0 ≤ 1
<span>2 ≤ 1 </span>
<span>4 - 2 * (-2) ≤ 1 </span>
<span>8 ≤ 1 </span>
<span>4 - 2 * (1) ≤ 1 </span>
<span>2 ≤ 1 </span>
<span>0 - 2 * 5 ≤ 1 </span>
<span>-10 ≤ 1 </span>
<span>(TRUE</span>
Firstly, for it to be a trinomial the expression would have to be x^2+5x+6 to factor this we would simply have to find 2 numbers that add up to 5 and multiply to 6. 3+2=5 and 3•2=6 so (x+3)(x+2) would be the answer
Answer:
The line of symmetry is x = 3
Step-by-step explanation:
To find the line of symmetry in this case, use the base formula for vertex form.
y = a(x - h) + k
In this formula, h is the line of symmetry. In this case, h is 3.
Answer:
Option C)
Step-by-step explanation:
Here we are given with the expression
The GCF of and 12 is 3
Hence we take 3 as GCF and bring it in front of the bracket.
It can not be factorise furthure as there is no GCF of 25 and also there is no rule for sum of squares so that we may apply it on this. Hence the answer would be
Option C)
Answer: m
explanation: jsjwjwjsiw